A Distinct T Follicular Helper Cell Subset Infiltrates the Brain in Murine Neuropsychiatric Lupus - Jain, Shweta; Stock, Ariel; Macian, Fernando; Putterman, Chaim (Frontiers in Immunology, 2018)
Neuropsychiatric symptoms in systemic lupus erythematosus are not uncommon, yet the mechanisms underlying disease initiation and progression in the brain are incompletely understood. Although the role of T cells in other lupus target organs such as the kidney is well defined, which T cells contribute to the pathogenesis of neuropsychiatric systemic lupus erythematosus is not known. The present study was aimed at characterizing the CD4 T cell populations that are present in the choroid plexus of MRL/MpJ-faslpr mice, the primary site of brain infiltration in this classic lupus mouse model which exhibits a prominent neurobehavioral phenotype. T cells infiltrating the choroid plexus of MRL/MpJ-faslpr mice were characterized and subset identification was done by multiparameter flow cytometry. We found that the infiltrating CD4 T cells are activated and have an effector function. Importantly, CD4 T cells have a T follicular helper cell (TFH) like phenotype, as evidenced by their surface markers and signature cytokine, IL-21. In addition, CD4 TFH cells also secrete significant levels of IFN-γ and express Bcl-6, thereby conforming to a pathogenic T helper population that can drive the disease progression. Interestingly, the regulatory axis comprising CD4 T regulatory cells is diminished. These results imply that accumulation of pathogenic CD4 T follicular helper cells in the brain of MRL/MpJ-faslpr mice contributes to the neuropsychiatric manifestations of systemic lupus erythematosus, and suggest this T cell subset as a novel therapeutic candidate.